Sward Structure, Light Interception, and Rhizome‐Root Responses of Rhizoma Peanut Cultivars and Germplasm to Grazing Management. Issue 2 (1st March 2016) - Mullenix, M. Kimberly; Sollenberger, Lynn E.; Wallau, Marcelo O.; Rowland, Diane L.; Blount, Ann R.; Vendramini, João M.B.; Silveira, Maria L.
Abstract : 'Florigraze' rhizoma peanut (RP; Arachis glabrata Benth.) is a persistent forage legume for the US Gulf Coast, but peanut stunt virus ( Cucumovirus spp.) reduces herbage accumulation (HA). Less susceptible germplasms and cultivars of RP have been released, but their responses to grazing management are not known. The objective was to quantify aboveground and belowground sward responses to grazing management of RP entries differing in growth habit to explain HA and persistence. Treatments were all combinations of four RP entries (Florigraze, 'UF Peace', 'UF Tito', and germplasm Ecoturf), two grazing intensities (50 and 75% removal of pre‐grazing canopy height), and two regrowth intervals (3 or 6 wk). UF Tito swards were the tallest and Ecoturf the shortest, but Ecoturf had greater herbage bulk density than any entry. Pre‐grazing leaf percentage was greatest for Ecoturf (61%); there were no differences among the upright entries (56–57%). Ecoturf (0.88) and UF Tito (0.76) had greater post‐grazing residual leaf area index than Florigraze (0.61). Ecoturf and UF Tito had greater rhizome‐root mass (4450 and 4110 kg ha ‐1, respectively) than Florigraze and UF Peace (3490 and 3170 kg ha ‐1, respectively). Pre‐grazing light interception was greater for the 6‐ than 3‐wk grazing frequency (85 vs. 70%, respectively), and rhizome‐root mass followed a similar pattern (3990 vs. 2730 kg ha ‐1, respectively). Sward structure, leaf, and rhizome‐root data explain lack of differences among entries in HA, excellent persistence of Ecoturf and UF Tito, and generally greater HA and persistence for 6‐ vs. 3‐wk regrowth intervals.